Autopsy Education in Canadian Pathology Programs: A Survey of Canadian Trainees. (September 2021) - Multan, Michael; Alakija, Pauline; Orde, Matthew; White, Steven
Abstract : Introduction: This survey of Canadian pathology residents was designed to quantify the number of autopsies Canadian residents aim to complete during residency training, to better understand the perception of residents about access and quality of autopsy skills education. In addition, the interest of current pathology residents in autopsy and forensic pathology as a future career was also assessed. Methods: A web-based survey was sent to all Canadian pathology residents. This survey consisted of 19 questions on institution, level of training, intention to complete the American Board of Pathology examination, number of autopsies completed, perception of quality/access to autopsy skills education, interest, and factors contributing to autopsy and forensic pathology. Results: Eighty two (26%) of a possible 310 residents (12/47 general pathology, 70/263 anatomical pathology) across all Canadian institutions offering anatomical or general pathology programs (16/16 institutions) participated in the survey. Eighty-three percent of the respondents rated autopsy education as either very important or important. Fifty-five percent of the respondents intended to either challenge the American Board of Pathology examination or wanted the option to do so in the future, whereas only 47% of the participants agreed that all residents who wish to challenge the examination will easily be able to complete 50 autopsies during residency. Only 18% of the respondents were interested in performing autopsies as a major part of their career, and a combined 52% were only interested in performing autopsies to secure a desired position or felt that having to do autopsies would be a job deterrent. The quality of autopsy teaching received and the number of autopsies performed was identified as the most significant factors affecting interest in performing autopsies as part of a future career. A combined 68% of the respondents felt that the job market in forensic pathology in Canada was either good (better than most subspecialties) or very good (more jobs than graduating fellows). Seventy-one percent (12/17) of postgraduate year 5 respondents reported having completed 50 or more autopsies at the time of survey completion. Eleven percent of the respondents did not agree that all residents who document having completed an autopsy at their institution will have participated in all 8 essential autopsy tasks. Twenty four (29%) of the 82 respondents provided detailed narrative comments. Discussion: Most Canadian pathology residents believe that autopsy education is an important component of residency training. Limited access to quality autopsy teaching seems to be an important factor in resident interest in forensic pathology as a future career, despite a perceived good job market in comparison with most other subspecialties.